Guidance of collective cell migration by substrate geometry - Doxzen, Kevin; Vedula, Sri Ram Krishna; Leong, Man Chun; Hirata, Hiroaki; Gov, Nir S.; Kabla, Alexandre J.; Ladoux, Benoît; Lim, Chwee Teck (Integrative Biology, 2013)
Collective behavior refers to the emergence of complex migration patterns over scales larger than those of the individual elements constituting a system. It plays a pivotal role in biological systems in regulating various processes such as gastrulation, morphogenesis and tissue organization. Here, by combining experimental approaches and numerical modeling, we explore the role of cell density (“crowding”), strength of intercellular adhesion (“cohesion”) and boundary conditions imposed by extracellular matrix (ECM) proteins (“constraints”) in regulating the emergence of collective behavior within epithelial cell sheets. Our results show that the geometrical confinement of cells into well-defined circles induces a persistent, coordinated and synchronized rotation of cells that depends on cell density. The speed of such rotating large-scale movements slows down as the density increases. Furthermore, such collective rotation behavior depends on the size of the micropatterned circles: we observe a rotating motion of the overall cell population in the same direction for sizes of up to 200 μm. The rotating cells move as a solid body, with a uniform angular velocity. Interestingly, this upper limit leads to length scales that are similar to the natural correlation length observed for unconfined epithelial cell sheets. This behavior is strongly altered in cells that present a downregulation of adherens junctions and in cancerous cell types. We anticipate that our system provides a simple and easy approach to investigate collective cell behavior in a well-controlled and systematic manner. © 2013 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2024-02-19